Complete mitochondrial genome of Cyrenobatissa subsulcata (Veneroida:Corbiculidae) - Xin Liao; Chenghui Liu (Mitochondrial DNA. Part B. Resources, 2020)
In this study, we assembled one mitochondrial genome of Cyrenobatissa subsulcata from NovaSeq 6000 sequencing data. The complete mitochondrial genome of C. subsulcata was 18,074 bp in length, including 37 genes, which are 13 protein-coding genes, 22 transfer RNA genes, and two ribosomal RNA genes ((12S and 16S), which was similar as another Corbiculidae species, Corbicula fluminea. The overall base composition was 26.08% for A, 42.9% for T, 9.11% for C, and 21.91% for G. A phylogeny of 14 bivalves showed C. subsulcata was clustered within Corbiculidae.